Kebijakan Partai Politik Terhadap Caleg Perempuan pada Pemilu 2009 di Bangka Belitung - Sulaiman, Aimie (SOSIOLOGI, 2009)
Affirmative action is an advocacy effort to women in politic domain considering presence of gap between male and female representatives in parliaments. This legal intervention effort must be signified as contemporary action and access for women to participation in constellation of 2009 election. We expect that womenâ representations give policies, which consider womenâ interest. This study is titled âPolitical Party Policies in Preparing Female Legislative Candidates of 2009 Election in Bangka Belitungâ.This study objective was to identify internal and external political party policies in preparing female cadres of 2009 election, inhibitive and supportive factors for female politicians, and strategies of party campaign of Golkar and PDI Perjuangan parties . Methods used in this study were qualitative methods with descriptive-analytic approaches. Study objects were Golkar and PDI Perjuangan parties for party management in provincial level. Sources of data consisted of elements of KPUD, party leaders or party managerial personnel, female legislative candidates and female legislative members of 2004 election result. Considering that sources of date were established for interest to achieve, samples were taken purposively. Data were collected by interview, participant and non participant observer, and documentation of 2004 election result. Technique of data analysis was started by reduction, presentation and interpretation of data.Encouragement of female politic awareness is not sufficiently only solved constitutionally. There must be social, cultural and structural efforts in revising party-internal policy. These aspects contributed positively to construction of female existence in political domain. Problem would reverse when Article 214 of Law No. 10/2008 was canceled by Constitution Court relative to specification of legislative candidates. Most voices systems will complicate opportunity of female legislative candidates because most of them are not well-known by constituents; in addition, free fight competition causes unhealthy competition and illegal logic practices. Internal and external policies, when recruitment process of legislative candidates do not give significant effect so that opportunity of female legislative candidates to elect becomes less sufficient, make females more unable to compete against patriarchal domination. Appropriate campaign strategy can help achieve legislative candidate socialization process. Political enlightenment which is expected from presence of quota policy, finally becomes quasi because political decision made by Constitution Court is irrational or ambiguous policy. Reasons are that, epistemologically, quota must be given to proportional election system with sequential number system than most voices system with free fight competition.